Кариотип Phrynocephalus rossikowi shammakowi (Reptilia, Agamidae) - Манило, В.В.; Голубев, М.Л. (Вестник зоологии, 1993)
A description of caryotype of P. r. shamma-kowi (Central Karakum, Turkmenistan) is presented. Only 25 of 50 examined slices contain 48 acroccntric chromosomes, but the rest contain 46 acrocentric ones. The number of chromosomes is observed to vary on the slices of all 5 lizards examined (4 females and 1 male). I'hus, this number does not depend on the sex peculiarity.